The Effect of Work Engagement and Organizational Culture on Employee Performance with Job Satisfaction as A Mediating Variable at the Aceh One-Stop Integrated Service Office - Shiba, Adila; Djalil, Muslim A.; Amri, (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to analyze the influence of work engagement and organizational culture on employee performance, with job satisfaction serving as a mediating variable at the Aceh Investment and One-Stop Integrated Service Agency (DPMPTSP Aceh). The research population consisted of all 149 employees at DPMPTSP Aceh, and a census sampling method was employed, ensuring that all population members were included in the sample. Data were collected through a questionnaire measured using a Likert scale and analyzed using Structural Equation Modeling (SEM) with AMOS software. The results demonstrate that work engagement has a positive influence on job satisfaction, contributing 39.6%. In comparison, organizational culture exerts an even stronger positive impact on job satisfaction, contributing 71.7%. While neither work engagement nor organizational culture significantly affects employee performance, job satisfaction plays a critical role, positively influencing employee performance by an additional 77%. Moreover, this study reveals that job satisfaction fully mediates the effects of work engagement and organizational culture on employee performance. The findings suggest that enhancing employee performance depends on fostering work engagement, promoting a positive organizational culture, and increasing job satisfaction.